Borrelia burgdorferi sensu lato seroconversion after intravenous immunoglobulin treatment: A cohort study. (5th May 2021) - Lucke, Ilse M.; Vrijlandt, Amber; Lim, Johan; van der Kooi, Anneke J.; van Schaik, Ivo N.; Zaaijer, Hans L.; Hovius, Joppe W.; Eftimov, Filip
Abstract: Objective: Intravenous immunoglobulin (IVIg) consists of pooled donor immunoglobulins (IgG), possibly including anti‐ Borrelia burgdorferi ( Bb sl) antibodies. Apparent IVIg‐related Bb sl seroconversion could lead to incorrect diagnosis of Lyme borreliosis. This cohort study was designed to determine how often IVIg treatment leads to apparent Bb sl seroconversion and whether antibodies disappear post‐treatment. Methods: Sera from chronic inflammatory demyelinating polyneuropathy (CIDP) and myositis patients were analyzed, drawn pre‐treatment and 6–12 weeks after the start of IVIg. In patients with apparent seroconversion, follow‐up samples after treatment withdrawal were analyzed, if available. Patients treated with corticosteroids were included as controls. A two‐tier protocol was used for serological testing consisting of the C6 Lyme ELISA (Oxford Immunotec) and confirmation by immunoglobulin M (IgM) and immunoglobulin G (IgG) immunoblot (Mikrogen ® ). Results: We included 61 patients: 51 patients were treated with IVIg and 10 with dexamethasone. Of the patients treated with IVIg, 42 had CIDP (82%) and were treated with Nanogam ® (Sanquin Plasma Products). Nine patients had myositis (18%) and were treated with Privigen ® (CSL Behring). Anti‐ Bb sl IgG seroprevalence pre‐treatment was 3% (2/61). Apparent seroconversion during IVIg treatment occurred in 39% (20/51) of patients, all treated with Nanogam. Post‐treatment seroreversion occurred in 92% (12/13) of patients with available follow‐up samples; in 78% (7/9) seroreversion was observed within 3 months. Conclusions: Transient presence of anti‐ Bb sl IgG antibodies after IVIg is regularly observed. This effect appears to be dependent on the IVIg brand, probably reflecting variation in Bb sl exposure of plasma donors. Lyme borreliosis serological testing during, and weeks to months after, IVIg is therefore of limited utility. Abstract : Presence of anti‐ Borrelia burgdorferi (Bb sl) antibodies after intravenous immunoglobulin (IVIg) was tested in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) and myositis. Transient presence of anti‐ Bb sl IgG antibodies after IVIg was regularly observed. This effect appears to be dependent on the IVIg brand, probably reflecting variation in Bb sl exposure of plasma donors. Lyme borreliosis serological testing during, and weeks to months after, IVIg is therefore of limited utility.